Regional modeling of climate change impacts on smallholder agriculture and ecosystems in Central America - Hannah, Lee; Donatti, Camila I.; Harvey, Celia A.; Alfaro, Eric; Rodríguez, Daniel Andres; Bouroncle, Claudia; Castellanos, Edwin; Díaz, Freddy; Fung, Emily; Hidalgo, Hugo G.; Imbach, Pablo; Läderach, Peter R.D.; et al. (Springer, 2017)
Climate change will have serious repercussions for agriculture, ecosystems, and farmer livelihoods in Central America. Smallholder farmers are particularly vulnerable due to their reliance on agriculture and ecosystem services for their livelihoods. There is an urgent need to develop national and local adaptation responses to reduce these impacts, yet evidence from historical climate change is fragmentary. Modeling efforts help bridge this gap. Here, we review the past decade of research on agricultural and ecological climate change impact